1997
DOI: 10.1021/ja9723390
|View full text |Cite
|
Sign up to set email alerts
|

Singlet−Triplet Splittings and 1,2-Hydrogen Shift Barriers for Methylphenylborenide, Methylphenylcarbene, and Methylphenylnitrenium in the Gas Phase and Solution. What a Difference a Charge Makes

Abstract: In the isoelectronic series methylphenylborenide, methylphenylcarbene, and methylphenylnitrenium, fundamental differences are predicted for singlet state geometries, singlet-triplet state splittings, barriers to singlet 1,2-hydrogen migration, and sensitivity of 1,2-hydrogen migration to solvent effects in n-heptane and acetonitrile. We conclude that isoelectronic analogies are dangerous for systems having different formal charges, and that the interaction of the divalent center with a conjugating substituent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
71
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(83 citation statements)
references
References 91 publications
11
71
1
Order By: Relevance
“…47 This and related DFT functionals have been shown to give quite reasonable agreement with experiment for related reactive intermediates such as carbenes and nitrenium ions. [48][49][50] ' RESULTS AND DISCUSSION Electronic State Orderings of the Phenyloxenium Ion. As shown in Table 1, the singlet-triplet gap (ΔE ST ) of the phenyloxenium ion 1 is computed to be 22.1 kcal/mol ( 1 A 1 -3 A 2 ).…”
Section: ' Computational Methodsmentioning
confidence: 99%
“…47 This and related DFT functionals have been shown to give quite reasonable agreement with experiment for related reactive intermediates such as carbenes and nitrenium ions. [48][49][50] ' RESULTS AND DISCUSSION Electronic State Orderings of the Phenyloxenium Ion. As shown in Table 1, the singlet-triplet gap (ΔE ST ) of the phenyloxenium ion 1 is computed to be 22.1 kcal/mol ( 1 A 1 -3 A 2 ).…”
Section: ' Computational Methodsmentioning
confidence: 99%
“…The compound is 4.0 kcal mol À1 more stable than 'Möbius benzene' 5 (see Pathway I). According to previous experimental and theoretical investigations, intramolecular rearrangements in carbenes proceed via the singlest state 11,12,[37][38][39] and therefore the further mechanistic considerations are restricted to the singlest state of 8.…”
Section: Intermolecular [4 2] Cycloaddition Reaction Of Conjugated Enmentioning
confidence: 99%
“…This was noted in our earlier AM1 study and is a consequence of the electronegativity difference between carbon and nitrogen. 9 In a recent DFT study, Cramer et al 35 found that markedly different chemical and electronic properties were predicted for the isoelectronic Ž y q . species, PhXMe X s B , C, N .…”
Section: Insights From Pmo Theorymentioning
confidence: 99%